Arabidopsis SNAREs SYP61 and SYP121 Coordinate the Trafficking of Plasma Membrane Aquaporin PIP2;7 to Modulate the Cell Membrane Water Permeability. Issue 7 (31st July 2014) - Hachez, Charles; Laloux, Timothée; Reinhardt, Hagen; Cavez, Damien; Degand, Hervé; Grefen, Christopher; De Rycke, Riet; Inzé, Dirk; Blatt, Michael R.; Russinova, Eugenia; Chaumont, François
Abstract : This work shows that the post-Golgi trafficking of PIP2;7 involves an interaction with SYP61 and SYP121 and that SYP61 and SYP121 colocalize and are physically associated in a SNARE complex. These findings suggest that SNAREs, and possibly a SYP61/SYP121 SNARE complex, play an important role in the regulation of the transport of the plasma membrane aquaporin. Abstract: Plant plasma membrane intrinsic proteins (PIPs) are aquaporins that facilitate the passive movement of water and small neutral solutes through biological membranes. Here, we report that post-Golgi trafficking of PIP2;7 in Arabidopsis thaliana involves specific interactions with two syntaxin proteins, namely, the Qc-SNARE SYP61 and the Qa-SNARE SYP121, that the proper delivery of PIP2;7 to the plasma membrane depends on the activity of the two SNAREs, and that the SNAREs colocalize and physically interact. These findings are indicative of an important role for SYP61 and SYP121, possibly forming a SNARE complex. Our data support a model in which direct interactions between specific SNARE proteins and PIP aquaporins modulate their post-Golgi trafficking and thus contribute to the fine-tuning of the water permeability of the plasma membrane.